A synthesis of overlapping and divergent areas of the resource-based view of the firm and entrepreneurship theory - Tamara Šmaguc (UTMS Journal of Economics, 2022)
The objectives of the paper are aimed at examining, identifying and elaborating the key points of overlapping and divergence of the ideas of the resource-based view of the firm and entrepreneurship. In the conditions when literature is not saturated related to the subject matter, the original and complete systematization of common and divergent features of the two paradigms is a valuable contribution to the theory of entrepreneurship. The paper is based on a reading and critical analysis of the existing scientific opus related to the thematic area. The conducted literature review resulted in the identification of several areas of overlapping and divergence of ideas of the resource-based view of the firm and entrepreneurship. The results of the review are presented by the author through a tabular approach, which is supplement with a descriptive elaboration. The findings confirm that the resource-based view of the firm represents a good conceptual basis for empirical research of the entrepreneurial process. In accordance with the results, the author offers a set of theoretical assumptions that serve as a conceptual basis for the design of empirical research on the role of capital in entrepreneurship.
Keywords: M10; M13; 330; resource-based view of the firm; theory of entrepreneurship; entrepreneurial capital; enterpriseresources